Definition of optimal driving range of electric vehicle considering its main parameters - Слипченко, Николай Иванович; Письменецкий, Виктор Александрович; Гуртовой, Михаил Юрьевич; Махлова, Вера Олеговна (Eastern-European Journal of Enterprise Technologies, 2013)
Simulation of electric vehicle (EV) operation modes allows evaluation of important parameters such as driving range, acceleration, capacity and type of storage battery. At present time, analytical dependences of EV mileage on the depth of battery discharge are virtually absent. The task of analyzing and modeling EV parameters and features is of current importance and practical interest to developers and automakers. Based on driving range simulation algorithm, computational experiment was conducted with further analysis of experimental data. Analysis and modeling of the EV main parameters provided concrete results of dependences of battery discharge depth on driving range for different payload masses. It is shown that driving range decreases with increasing payload mass in a standard urban driving cycle. The study of dependence of driving range on battery capacity and EV speed was conducted by regression method. The paper gives the search for the EV speed and battery capacity optimal values by the maximum driving range criterion according to the method of gradient descent. As a result of two-parameter optimization the optimal speed values of EV with the mass of 1.4 tones were obtained (30 km/h and 85 A/h)